2007
DOI: 10.1016/j.saa.2006.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Raman spectroscopic study of the molecular structure of the uranyl mineral zippeite from Jáchymov (Joachimsthal), Czech Republic

Abstract: (2007) Raman spectroscopic study of the molecular structure of the uranyl mineral zippeite from Jáchymov (Joachimsthal), Czech Republic. Spectrochimica Acta Part A 67(5):1220 -1227. ) Å. Calculated U-O bond lengths are in agreement with U-O bond lengths from the single crystal structure analysis and those inferred for uranyl anion sheet topology of uranyl pentagonal dipyramidal coordination polyhedra. The number of observed bands supports the conclusion from single crystal structure analysis that at least two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…The spectral region from 400 to 700 cm −1 is usually attributed to bending activity of sulphate anions; however these bands are not very distinct except one at 398 cm −1 . There is also one more shift of unknown origin, which presence in the zippeite spectrum was not confirmed in literature [14][15][16].…”
Section: Collection Of Secondary Uranium Mineralsmentioning
confidence: 70%
See 1 more Smart Citation
“…The spectral region from 400 to 700 cm −1 is usually attributed to bending activity of sulphate anions; however these bands are not very distinct except one at 398 cm −1 . There is also one more shift of unknown origin, which presence in the zippeite spectrum was not confirmed in literature [14][15][16].…”
Section: Collection Of Secondary Uranium Mineralsmentioning
confidence: 70%
“…The Raman spectrum of zippeite presented in Fig. 2 exhibits typical features for zippeite [14][15][16] such as 1012 cm −1 shift attributed to a symmetric stretching vibration of (SO 4 ) 2− group and 1091 cm −1 of antisymmetric one. An intense band of 842 cm −1 , with two others overlapping from the shorter wavelength side, are caused by symmetric stretching of the (UO 2 ) 2+ group.…”
Section: Collection Of Secondary Uranium Mineralsmentioning
confidence: 98%
“…The topology of the zippeite sheet thus is compatible with a wide range of interlayer configurations and water molecules contents. [5,6] A zippeite-type mineral having the proposed composition K 0.6 (H 3 O) 0.4 [(UO 2 ) 6 (SO 4 ) 3 (OH) 7 ]·8H 2 O, was recently described by Frost et al [7,8] Relatively low contents of divalent cations (Mg, Ca, Fe), found in the studied sample, were omitted and the charge balance between the sheets and the interlayer was solved by inclusion of hydroxonium cations in the formula. The presence of hydroxonium was supported by Raman and infrared spectra.…”
Section: Introductionmentioning
confidence: 99%
“…A recent paper by Peeters et al [5] and a recently made available thesis by McCollam [6] prove the presence of monovalent and divalent cations together contained in crystal structures of some synthetic and natural zippeites. It could be therefore inferred that such divalent cations may be present in the zippeite-type mineral studied and should be therefore included in the crystal structure and chemical formula of this phase described by Frost et al [7,8] As far as we know the crystal structural analysis has been not available as yet for natural zippeite (K-zippeite). However, the X-ray single crystal structure of marecottite, Mg 3 (H 2 O) 18 [9] and the partial structure of pseudojohannite, Cu 6.5 [(UO 2 ) 4 O 4 (SO 4 ) 2 ] 2 ·25H 2 O [10] have been published.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation